Fulfillment of Legal Rights Protection on Incentives and Allowances for Indonesian Health Professionals during the COVID-19 Pandemic - Wiwoho, Jamal; Firdaus, Sunny Ummul; Hidayat, Muhamad Alief (HUKUM PEMBANGUNAN EKONOMI, 2023)
The problem relies on the suboptimal fulfillment of incentives and allowances for Indonesian health professionals. It becomes urgency that health professionals are the front liner in the treatment and countermeasures of COVID-19, especially with the high work risk burden that is faced, thus, making the government strive to fulfill at its best. The problem always repeats due to an unsynchronized implementation by the central and the local government until now, so it also worsens the unfulfilled rights of health professionals. The method used in this research was the socio-legal method. The data were collected from the existing laws and regulations and the result from sociological observation. The results indicated that there is a study on rights fulfillment for health professionals based on the laws of the rights of health professionals in Indonesia. The study elaborates on the problem that is currently happening with COVID-19 cases in Indonesia and the reality of the rights fulfillment of health professionals. This article also discusses legal reality in the making of laws and regulations das sollen and das sein.